(untitled) (Revista Estudios Psicológicos, 2023)
The percentage of female offenders, compared to men, has historically been extremely low; however, the social stigma towards female offenders is stronger than that applied to men. The objective of this research was to propose a general typology of women who commit crimes, adapted to the 21st century. This research was carried out through the qualitative paradigm, with a descriptive methodology. An exhaustive documentary review was applied where the main inclusion criteria were articles on the role of women as criminals, exclusively, throughout various historical moments. It was identified that many of the investigations, although they begin seeking to explain the woman as a criminal, mostly always end up exposing or focusing on the woman as a victim, that is, justifying her actions. There are some common characteristics in the cases of criminals that allow to broadly define the criminological profile of the woman offender of the law, in this documentary review the most outstanding elements were selected. Ten large groups of women were identified, classified according to crimes committed. These categories are: shoplifter, drug dealer, bearer of weapons and objects from crime, pimp or head of human trafficking networks, filicide, child abuser, passion murderer, fraudster, insulting men and rebellious or violent. In conclusion, it can be said that this theory belonging to the area of ​​female criminology is adapted to the reality of the 21st century.